Intelligent traction control system of an electric golf car: nonlinear dynamics investigation - Rahman, Mohammed Ataur; Mohiuddin, A. K. M. (2011)
Intelligent traction control system of an electric golf car has been developed by using the experience of the traction in order to maintain the golf car traction as required with utilizing optimum power. Compared with conventional control approach, fuzzy logic approach is more efficient for nonlinear dynamic systems and embedding existing structured human knowledge into workable mathematics. The purpose of this study is to investigate the relationship between vehicle’s input parameters of power supply (PI) and moisture content (MC) and output parameter of traction force (TF) and Power Consumption (P). Experiment has been conducted in the field to investigate the vehicle traction and the result has been compared with the developed fuzzy logic system (FLS) based on Mamdani approach. Results show that the mean relative error of actual and predicted values from the FLS model on TF is found as 7.68 %, which is less than the acceptable limit of 10%. The goodness of fit of the prediction value from FLS is found close to 1.0 as expected and hence shows the good performance of the developed system.